Research and design of doubly salient permanent magnet motor for hybrid electric vehicle based on the NdFeB permanent magnet material. (November 2015) - Lian, J.; Chang, J.; Li, L.; Zhou, Y.; Mi, M.
Abstract : The performance of hybrid electric vehicle motor directly affects its power performance and fuel economy. The high performance sintered NdFeB permanent magnet material is chosen as the core material of the hybrid vehicle motor for the design of the permanent magnet in this paper, and its size is also determined. A doubly salient permanent magnet motor is proposed here on the basis of the selected NdFeB permanent magnet material, and its structure size is designed. The finite element numerical calculation is carried out for the motor in particular rotor position angle on the basis of the field quantity to obtain the magnetic field distribution law in several typical rotor positions and the static characterise parameters of the motor are further obtained. Final, inspect the performance of the prototype objectively based on the bench experiment of the designed physical prototype, and the prototype experiment and finite element results both proved that the designed doubly salient permanent magnet motor could meet the requirements of hybrid electric vehicle, so as to achieve the purpose of the research and design of the doubly salient permanent magnet motor used in hybrid electric vehicle.